SISTEM INFORMASI PENJUALAN MOBIL BERBASIS WEBSITE PADA CV. MULYA SEDAYA MOTOR - Refa Yudhatama Ramadhan (2021)
The condition of each used car has advantages and disadvantages, with varying specifications and features including in terms of price, type, transmission, technology, features, engine capacity, and others. By only still relying on brochures resulted in the ineffectiveness of the sales system that is currently used. This often makes consumers find it difficult to see the cars available at the Mulya Sedaya Motor Showroom, because this also results in a decline in sales from the Mulya Sedaya Motor showroom. This study uses the PIECES approach, UML design and applications for web design using PHP and MySQL programming. A website-based car sales information system at the Mulya Sedaya Motor showroom, can help potential consumers to see the available cars without having to come directly to the showroom.